Examining the impact of problem-based learning on students’ motivation and social studies learning outcomes in junior high schools - Iis Widayati (Jurnal Inovasi Guru Indonesia, 2026)
Background: Social Studies education at the junior high school level requires instructional strategies that enhance students’ motivation and improve academic achievement in alignment with student-centered learning principles. Problem-Based Learning (PBL) has been widely recognized as an active learning model that promotes engagement, critical thinking, and meaningful knowledge construction. However, empirical evidence examining its simultaneous impact on students’ motivation and Social Studies learning outcomes at the junior secondary level remains limited. Objective: This study aimed to examine the impact of Problem-Based Learning on students’ learning motivation and Social Studies learning outcomes in junior high schools. Methods: The study employed a quantitative quasi-experimental design with a non-equivalent control group pretest–posttest format. A total of 64 eighth-grade students were divided into an experimental group receiving PBL instruction and a control group receiving conventional teaching. Data were collected using a validated learning motivation questionnaire and a Social Studies achievement test. Data analysis included descriptive statistics, paired samples t-tests, independent samples t-tests, and effect size calculations. Results: The findings revealed a significant increase in students’ motivation and learning outcomes in the experimental group compared to the control group (p < 0.05). The experimental group demonstrated a higher posttest mean score in both motivation and academic achievement. The calculated effect size indicated a large practical impact of PBL on Social Studies learning outcomes. Conclusion: Problem-Based Learning significantly enhances students’ motivation and academic performance in junior high school Social Studies classrooms. The implementation of PBL provides meaningful, student-centered learning experiences that foster engagement and deeper conceptual understanding.